Minkowski Space : The Spacetime of Special Relativity - Schröter, Joachim (De Gruyter Studies in Mathematical Physics ;, 2017)
In Minkowski-Space the space-time of special relativity is discussed on the basis of fundamental results of space-time theory. This idea has the consequence that the Minkowski-space can be characterized by 5 axioms, which determine its geometrical and kinematical structure completely. In this sense Minkowski-Space is a prolegomenon for the formulation of other branches of special relativity, like mechanics, electrodynamics, thermodynamics etc. But these applications are not subjects of this book. Contents Basic properties of special relativityFurther properties of Lorentz matricesFurther properties of Lorentz transformationsDecomposition of Lorentz matrices and Lorentz transformationsFurther structures on MsTangent vectors in MsOrientationKinematics on MsSome basic notions of relativistic theories